A Heat Demand Load Curve Model of the Swiss National Territory. (June 2019) - Schneider, S; Hollmuller, P; Chambers, J; Patel, M
Abstract: This paper presents a bottom up model simulating the hourly heat demand load curve for space heating and domestic hot water production for Swiss buildings listed in the national building and dwelling register. The model was calibrated on the actual heat demand load curves of several building types and predicts the demand as function of external temperature and solar irradiation. In addition, it includes stochastic deviations to accurately reproduce the aggregated load of large building groups. Using a climatic database covering the whole Swiss territory, the model takes account of the diverse weather conditions and climate types. The aggregated simulated load curve is compared with the measurements from a large district heating network, demonstrating that key indicators such as peak load and ranked loads are very well reproduced. To disseminate the results, a GIS database was setup that estimates the aggregated heat demand load curve for any portion of the Swiss national territory. The proposed approach addresses the challenge of large territorial scale simulation using only limited information available on its building stock. The model can be easily adapted to generate load curves for other EU regions provided the required information is available for the building stock.